Levitation and guidance force efficiencies of bulk YBCO for different permanent magnetic guideways - Abdioglu, M.; Ozturk, K.; Gedikli, H.; Ekici, M.; Cansiz, A. (Elsevier BV, 2015)
Abstract The development of superconductor Maglev systems depends on various disciplinary studies due to the inherent composition of available technologies. Because the fabrication cost is very effective on the Maglev, the requirement of the efficiency improvement focuses the researchers on the design considerations. In this study, the guidance force, the magnetic levitation force (MLF) and magnetic stiffness of different permanent magnetic guideway (PMG) arrangements were investigated in different cooling heights (CH) to enhance the efficiency of Maglev system. The single domain cylindrical bulk YBCO superconductors fabricated by top seeding method with the diameter of 45 mm and the height of 15 mm were used as HTS. Magnetic field distributions of the PMGs were calculated by finite element method to determine optimum HTS–PMG arrangements. We have used auxiliary onboard permanent magnets with YBCOs to improve the MLF of three pole Halbach PMG arrangements. It is seen that the efficiency of Maglev systems can be improved by using suitable HTS–PMG arrangements. In this study cost efficiency of the integrated levitation and guidance force (( F z ) max ( F x ) max /( S PMG  ∗ Cost)) was also determined. It is inferred from this study that the cooling height and PMG–HTS arrangement are key parameters for guidance force, levitation force, magnetic stiffness and efficiency of Maglev systems. It is believed that this study will supply useful references for practical application of HTS Maglev systems.
Keywords: Finite element method; Yttrium barium copper oxides; Permanent magnets; Levitation force; Efficiency; Superconducting materials; Magnetic field distribution; Stiffness; Maglev; Permanent magnetic guideway; Design considerations; Magnetic levitation force; High-Tc superconductors; Guideways; Magnetic devices; Magnetism; Costs; Cooling systems; Efficiency improvement; Magnetic levitation; Magnetic levitation vehicles; High-T